Anatomy of nasal complex in the southern right whale, Eubalaena australis (Cetacea, Mysticeti) - Buono, Mónica Romina (2015)
The nasal region of the skull has undergone dramatic changes during the course of cetacean evolution. In particular, mysticetes (baleen whales) conserve the nasal mammalian pattern associated with the secondary function of olfaction, and lack the sound-producing specializations present in odontocetes (toothed whales, dolphins and porpoises). To improve our understanding of the morphology of the nasal region of mysticetes, we investigate the nasal anatomy, osteology and myology of the southern right whale, Eubalaena australis, and make comparisons with other mysticetes. In E. australis external deflection surfaces around the blowholes appear to divert water off the head, and differ in appearance from those observed in balaenopterids, eschrichtiids and cetotherids. In E. australis the blowholes are placed above hypertrophied nasal soft tissues formed by fat and nasal muscles, a pattern also observed in balaenopterids (rorqual mysticetes) and a cetotherid (pygmy right whale, Caperea marginata). Blowhole movements are due to the action of five nasofacial muscles: dilator naris superficialis, dilator naris profundus, depressor alae nasi, constrictor naris, and retractor alae nasi. The dilator naris profundus found in E. australis has not been previously reported in balaenopterids. The other nasofacial muscles have a similar arrangement in balaenopterids, with minor differences. A novel structure, not reported previously in any mysticete, is the presence of a vascular tissue (rete mirabile) covering the lower nasal passage. This vascular tissue could play a role in warming inspired air, or may engorge to accommodate loss of respiratory space volume due to gas compression from increased pressure during diving.